2021
DOI: 10.1259/bjr.20210188
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics features on ultrasound imaging for the prediction of disease-free survival in triple negative breast cancer: a multi-institutional study

Abstract: Objectives: To explore the predictive value of radiomics nomogram using pretreatment ultrasound for disease-free survival (DFS) after resection of triple negative breast cancer (TNBC). Methods and materials: A total of 486 TNBC patients from 3 different institutions were consecutively recruited for this study. They were categorized into the primary cohort (n = 216), as well as the internal validation cohort (n = 108) and external validation cohort (n = 162). In primary cohort, least absolute shrinkage and sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…Consistent with previous studies [ 14 , 34 36 ], we found that TNBC patients with more metastatic axillary lymph nodes had a worse prognosis. This is expected because the number of positive lymph nodes determines the pathological stage of breast cancer and is important predictor of survival outcomes [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous studies [ 14 , 34 36 ], we found that TNBC patients with more metastatic axillary lymph nodes had a worse prognosis. This is expected because the number of positive lymph nodes determines the pathological stage of breast cancer and is important predictor of survival outcomes [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…Among these patients, those with high levels of stromal tumor-infiltrating lymphocytes in the early stage had excellent survival outcomes; thus, a subset of TNBC patients could be spare adjuvant chemotherapy [32,33]. Consistent with previous studies [14,[34][35][36], we found that TNBC patients with more metastatic axillary lymph nodes had a worse prognosis. This is expected because the number of positive lymph nodes determines the pathological stage of breast cancer and is important predictor of survival outcomes [37].…”
Section: Tnbc Is Well Known To Have Poor Outcomes Owing To Its Aggres...supporting
confidence: 89%
“…Wavelet features have been previously mentioned in the response prediction of colorectal cancer [ 31 ], but their application in breast cancer treatment response remain unexplored., which is worthy of further investigation. Moreover, the addition of clinicopathological data has been reported to increase the predictive ability compared to that of the model alone [ 32 ], but external validation has failed to confirm the superiority of the radiomic model over the clinical model [ 29 ]. In our study, we also failed to show a significant improvement in pCR prediction with the addition of clinical factors.…”
Section: Discussionmentioning
confidence: 99%
“…The nomogram had superior predictive power to the clinicopathological marrow and the number-based prediction of metastatic lymph nodes. The authors conclude that the addition of clinicopathological data to the radiomic model increases the power of prediction compared to any of the independently evaluated models [72].…”
Section: Prognosis and Prediction Of Response To Neoadjuvant Chemothe...mentioning
confidence: 93%
“…Radiomics for TNBC: the table includes the imaging method chosen for radiomic analysis, the type, the number of features used in creating the model including the radiomic score and nomograms, study objectives, authors and year of publication[58,[62][63][64][65][66][67][68][69][70][71][72][73][74].…”
mentioning
confidence: 99%